2011
DOI: 10.1007/s10147-011-0351-y
|View full text |Cite
|
Sign up to set email alerts
|

Cervical stromal involvement can predict survival in advanced endometrial carcinoma: a review of 67 patients

Abstract: Cervical stromal involvement is a poor prognostic factor in cases of advanced endometrial carcinoma. Further studies are required to describe the effect of different surgical approaches such as radical hysterectomy on survival in the presence of cervical stromal invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Age, histologic type, grade, depth of myometrial invasion, cervical involvement, lympho-vascular space invasion, presence or area of lymph node metastasis, the amount of the both removed and metastatic lymph nodes, presence of non-nodal extra-uterine disease and addition or type of adjuvant therapy were found to be important for survival (9,17,18,(21)(22)(23)(24)(25)(26)(27). In our study, it was found that independent prognostic factors in the patients receiving adjuvant radiotherapy were age for only recurrence and non-nodal extra-uterine disease for both recurrence and death.…”
Section: Discussionmentioning
confidence: 99%
“…Age, histologic type, grade, depth of myometrial invasion, cervical involvement, lympho-vascular space invasion, presence or area of lymph node metastasis, the amount of the both removed and metastatic lymph nodes, presence of non-nodal extra-uterine disease and addition or type of adjuvant therapy were found to be important for survival (9,17,18,(21)(22)(23)(24)(25)(26)(27). In our study, it was found that independent prognostic factors in the patients receiving adjuvant radiotherapy were age for only recurrence and non-nodal extra-uterine disease for both recurrence and death.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical stromal invasion is associated with increased likelihood of pelvic lymphadenopathy 40,41 and an adverse prognosis. 42,43…”
Section: Endometrial Cancermentioning
confidence: 99%